Radiation Synthesis of Organostarch as Fluorescence Label - Alkhursani, Sheikha A.; Ghobashy, Mohamed Mohamady; Madani, Mohamed (Asian Journal of Chemistry, 2020)
Fluorescence label preparation, being the core of sensing and imaging, is the most interesting aspect of label technology. Using the gamma irradiation technique, a facial method is proposed to prepare organostarch consisting of polyaniline and starch. Polyaniline was introduced into starch molecules to form an inclusion complex between V-type starch and aniline monomer. The inclusion complex thus formed consisted of starch-aniline crosslink caused by gamma irradiation through organostarch crosslinks. Thus, organostarch develops fluorescence property at 470 nm possibly through the interaction of aniline and starch, which are both fluorophores. A comparative analysis of variations is performed in common fluorescent labels of starch and organostarch based on their physico-chemical properties. X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectrometry were utilized to confirm the inclusion of polyaniline into starch molecules. Furthermore, using a fluorescence microscope, the positive implementation of fluorescent organostarch was verified. Fluorescent organostarch can be synthesized through this simple method and can be widely used for developing biomarkers and biosensors in food and biomedical industries. Organostarch produces florescence under mild conditions even without complicated preparations, such as additives for labelling with dye fluorescence. The intensity of fluorescence of organostarch was 17,000 times that of natural starch.